Biological Preparation of Iron-Zinc Oxides Core-Shell (Fe3O4-ZnO) Nanoparticles Using Nerium oleander Extracts and Their Activities Against F. oxysporum f.sp. lycopersici - Khadum, M. J.; Yaaqoob, L. A. (Iraqi Journal of Science, 2026)
This study aimed to use Nerium oleander as a reducing and stabilizing agent for core-shell nanoparticles of iron and zinc (Fe3O4-ZnO) to use as an antimicrobial agent. The biosynthesized (Fe3O4-ZnO) NPs were characterized by various techniques such as UV-VIS, AFM, EDX, TEM, and Zeta potential. The wavelength of the (Fe3O4-ZnO) core-shell nanoparticles was (319 nm), the diameter was identified by atomic force microscopy (AFM), the average diameter was 78.74 nm, the core and shell nanoparticles (Fe3O4-ZnO) were confirmed by transmission electron microscopy (TEM) through the dark inner region representing the core and the bright part surrounding the dark region representing the shell and Zeta potential for (Fe3O4-ZnO) core-shell nanoparticles was 29.89- mV. For molecular diagnosis of Fusarium oxysporum f.sp. lycopersici, DNA was extracted to determine the identity of the isolate. The sample contained the target DNA fragments of 680 base pairs in size. The result was 100% identical in the NCBI GenBank database with F. oxysporum. The ITS rDNA sequence of the strain has been deposited in the NCBI GenBank database (GenBank accession numbers PQ060101). The antimicrobial activity of the core and shell nanoparticles (Fe3O4-ZnO) was recorded at 400 μg/mL with a maximum inhibition zone of 33 mm in diameter and minimum inhibition zone at 100 μg/mL with a diameter of 13 mm.